ANALISIS PERANCANGAN SISTEM INFORMASI PENDATAAN PEKERJA MENGGUNAKAN METODE WATERFALL - Bagus Emirsyach Yudhistira; Singgih Saptadi (Industrial Engineering Online Journal, 2023)
AbstractPT ITCI Hutani Manunggal is an Industrial Plantation Forest (HTI) company with the main crops Eucalyptus Sp. and Acacia mangium. In this study, observations were made on the information system for data collection of PT ITCI Hutani Manunggal workers, which still uses MS Excel in manual input. After observations were made on the information system of PT ITCI Hutani Manunggal, there was a problem regarding the lack of efficiency and effectiveness in the data collection of these workers. This problem causes losses for PT ITCI Hutani Manunggal, both material and non-material losses. Procurement of information systems to conduct data collection minimizes the potential for human error that may occur and makes the data collection process more efficient. Actors who play a role in the equipment monitoring system, namely System Admin, HR Leaders, and HR staff. The design of improving the information system on worker data collection is carried out using the waterfall method.Keywords: information system design, worker data collection, use case diagram, waterfall methodAbstractPT ITCI Hutani Manunggal is an Industrial Plantation Forest (HTI) company with the main crops Eucalyptus Sp. and Acacia mangium. In this study, observations were made on the information system for data collection of PT ITCI Hutani Manunggal workers, which still uses MS Excel in manual input. After observations were made on the information system of PT ITCI Hutani Manunggal, there was a problem regarding the lack of efficiency and effectiveness in the data collection of these workers. This problem causes losses for PT ITCI Hutani Manunggal, both material and non-material losses. Procurement of information systems to conduct data collection minimizes the potential for human error that may occur and makes the data collection process more efficient. Actors who play a role in the equipment monitoring system, namely System Admin, HR Leaders, and HR staff. The design of improving the information system on worker data collection is carried out using the waterfall method.Keywords: information system design, worker data collection, use case diagram, waterfall method